2017
DOI: 10.1016/j.celrep.2017.08.037
|View full text |Cite
|
Sign up to set email alerts
|

KIF5B-RET Oncoprotein Signals through a Multi-kinase Signaling Hub

Abstract: Summary Gene fusions are increasingly recognized as important cancer drivers. KIF5B-RET gene was recently identified as a primary driver in a subset of lung adenocarcinomas. Targeting human KIF5B-RET to epithelia in Drosophila directed multiple aspects of transformation including hyperproliferation, epithelial-to-mesenchymal transition, invasion, and extension of striking invadopodia-like processes. KIF5B-RET-transformed human bronchial cell line showed similar aspects of transformation including invadopodia-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 45 publications
4
45
0
Order By: Relevance
“…The presence of this ALK fusion may suggest that recurrences could be treated with ALK inhibitors such as crizotinib and ceritinib. However, there is evidence that the N-terminus domain of KIF5B fusion proteins can activate receptor tyrosine kinases (RTKs) independently of the C-terminus kinase domain in KIF5B-RET fusions, indicating a potential need to combine epidermal growth factor receptor inhibitors with ALK inhibitors in KIF5B-ALK fusions 3. Overall, our case highlights a novel ALK fusion with KIF5B in a rare inflammatory atypical myofibroblastic tumour of the CNS.…”
Section: Descriptionmentioning
confidence: 82%
“…The presence of this ALK fusion may suggest that recurrences could be treated with ALK inhibitors such as crizotinib and ceritinib. However, there is evidence that the N-terminus domain of KIF5B fusion proteins can activate receptor tyrosine kinases (RTKs) independently of the C-terminus kinase domain in KIF5B-RET fusions, indicating a potential need to combine epidermal growth factor receptor inhibitors with ALK inhibitors in KIF5B-ALK fusions 3. Overall, our case highlights a novel ALK fusion with KIF5B in a rare inflammatory atypical myofibroblastic tumour of the CNS.…”
Section: Descriptionmentioning
confidence: 82%
“…This was initially demonstrated in Drosophila models with CCDC6-RET and NCOA4-RET when these fusion genes were expressed in the epithelia during development (16). A study also using Drosophila models in addition to engineered human bronchial epithelial cells further revealed that the kinesin domain of KIF5B and the kinase domain of RET act together to form a multikinase (RET/EGFR/FGFR/SRC) signaling hub (17). This suggests that, rather than targeting RET alone, multiple kinase components of the KIF5B-RET signaling hub may need to be simultaneously targeted for optimal effect.…”
Section: Discussionmentioning
confidence: 95%
“…However, the fact that no KIF5B-RET fusion arose as a mechanism of resistance in this series suggests emergent KIF5B-RET fusions may not be tolerated in the presence of anti-EGFR TKI and/or that loss of CCDC6 or NCOA4 affords a particular survival advantage to tumors exposed to an EGFR TKI. In a Drosophila model, KIF5B-RET fusions (particularly the motor domain that is unique to KIF5B relative to the other fusion partners) are highly reliant on EGFR signaling to promote enhanced cell growth, more so than CCDC6-RET or NCOA4-RET fusions (50). There may be important cell biology differences based on the RET fusion partner.…”
Section: Discussionmentioning
confidence: 99%